THE INFLUENCE OF SERVICE QUALITY ON OUTPATIENT SATISFACTION AT THE TELUK BINTUNI HOSPITAL WHICH IS MEDIATED BY CULTURE AND BELIEFS - Wiendo Syahputra Yahya; Saparso; Fushen (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
In the highly competitive hospital industry, increasing patient satisfaction through service quality and trust is an important priority. This research is important to understand how service quality, trust, and culture influence outpatient satisfaction at Teluk Bintuni Regional Hospital. Information shows that there has been a decrease in the number of new outpatient visitors at Teluk Bintuni Regional Hospital from 2017 to 2020, reaching around 29.5%. The problem is that Teluk Bintuni Hospital faces challenges in increasing new outpatient visits, where factors such as service quality, trust, culture and customer satisfaction can be the cause. Evaluation of service quality is crucial to identify dimensions that need improvement. The decrease in the number of outpatients indicates a decrease in patient trust and the influence of culture that is not conducive to quality services. Therefore, this research aims to contribute new knowledge that can be used to develop strategies to improve the quality of health services at Teluk Bintuni Hospital, so that it can provide a positive experience for outpatients. This research aims to determine the influence of Service Quality on Outpatient Satisfaction at Teluk Bintuni Regional Hospital which is mediated by culture and beliefs. Located at Teluk Bintuni Hospital, there are 100 (one hundred) people and all members of the population are also samples so this research is a census research. The results of this analysis show that all indicators used in this research are valid and reliable. This research uses a Structural Equation Modeling (SEM) approach based on Partial Least Square (PLS) using SmartPLS 3.3 software. This research provides evidence of a positive and significant influence